2016
DOI: 10.1111/andr.12181
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of enzymatic and non‐enzymatic antioxidants in seminal plasma of men with genitourinary infections, varicocele and idiopathic infertility

Abstract: SUMMARYThis study was aimed to assess the antioxidant enzymatic and non-enzymatic compounds in semen of infertile men. Seventy-four infertile patients were grouped according to their clinical diagnosis: genitourinary infection, varicocele, idiopathic infertility. Semen samples of fertile men represent the control. Semen characteristics were evaluated by light and transmission electron microscopy (TEM). TEM data was quantified with a mathematical formula, which provides numerical scores. Spectrophotometric and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 40 publications
5
34
0
Order By: Relevance
“…The lipid peroxidation of the membrane and the rate of aniline blue-positive spermatozoa was significantly higher in the '2-months varicocoele group' compared to the controlsham groups. This result further reiterates on increased ROS production and altered chromatin maturity with varicocoele, as also reported in men [13,35,36]. Moreover, we found a non-significantly more sperm DNA fragmentation after varicocoele induction compared to the control-sham groups.…”
Section: Discussionsupporting
confidence: 90%
“…The lipid peroxidation of the membrane and the rate of aniline blue-positive spermatozoa was significantly higher in the '2-months varicocoele group' compared to the controlsham groups. This result further reiterates on increased ROS production and altered chromatin maturity with varicocoele, as also reported in men [13,35,36]. Moreover, we found a non-significantly more sperm DNA fragmentation after varicocoele induction compared to the control-sham groups.…”
Section: Discussionsupporting
confidence: 90%
“…As a result of this analysis, it can be stated that GSH / GSSG system status in the leukocytospermic samples does not undergo significant changes, since this group of patients was in a single cluster with the fertile normozoospermic men. The results are confirmed by data from other researchers who found that maintaining of GSH / GSSG homeostasis in spermatozoa of the infertile men with an infectious factor was associated with a "sparing effect" caused by other nonenzymatic antioxidants, in particular vitamin C [10]. Similar distribution by clusters was obtained by indices of the oxidative manifestations ( Fig.…”
Section: Resultssupporting
confidence: 88%
“…Varicocele group, as previously reported, was characterised by an elevate percentage of sperm immaturity (Collodel et al, 2018). Previously, sperm immaturity, necrosis and apoptosis were correlated to malondialdehyde and enzymatic and nonenzymatic antioxidant molecules in patients with varicocele, idiopathic infertility and genitourinary infections (Micheli et al, 2016).…”
Section: Discussionmentioning
confidence: 69%
“…In our field of expertise, semen parameters were evaluated as previously reported (Micheli et al, 2016). Samples were collected by masturbation after 3-5 days of sexual abstinence.…”
Section: Semen Analysis: Light and Electron Microscopymentioning
confidence: 99%